Application of Carbon Dioxide Supercritical Fluid Extraction of Heavy Metals from Ambient Aerosols - TALEBI, S.M.; ABEDI, M.; GHEISARI, M.M.; SABER-TEHRANI, M. (Asian Journal of Chemistry, 2010)
The possibility of using carbon dioxide supercritical fluid for extraction of trace heavy metals including; Pb, Cd, Cr, Cu, Ni and Zn from airborne particulate matter has been investigated. The effects of pressure, extraction time and mixed modifier on the extraction efficiencies of heavy metals were studied and the results showed that although all of these parameters enhance the extraction efficiencies, but using surfactants has improved the extraction efficiency considerably. Two different chelating agents were used for making complex from the heavy metals and it was cleared that diethyl dithiocarbamate (Na DDC) along with mixed modifier can be effectively used for extraction of Pb, Cd, Cu and Zn while dithizone (DT) along with mixed modifier showed capability for extraction of Cd, Cu and especially for Cr.